2008
DOI: 10.1177/1753193408087229
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Flexor Digitorum Superficialis Tendon in the Little Finger is not Associated with Decreased Grip Strength

Abstract: We examined the little finger in 402 normal subjects for the presence or absence of the flexor digitorum superficialis. All subjects also had their grip strength measured. No statistically significant difference was seen in the grip strength measurements between subjects who had a flexor digitorum superficialis tendon to the little finger and those who did not. This study demonstrates that absence of the flexor digitorum superficialis to the little finger is not associated with decreased grip strength. The imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
2
19
0
3
Order By: Relevance
“…Bowman et al [8] reported that those male and female subjects had similar frequencies of FDSabsent tendons. Similarly, Puhaindran et al [3] found similar frequencies in both sexes. Conversely, Wilcox et al [12] found that female subjects had more common absent function than male subjects.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Bowman et al [8] reported that those male and female subjects had similar frequencies of FDSabsent tendons. Similarly, Puhaindran et al [3] found similar frequencies in both sexes. Conversely, Wilcox et al [12] found that female subjects had more common absent function than male subjects.…”
Section: Discussionmentioning
confidence: 66%
“…Because these variants do not affect the functions of the hand regarding grip strength and activities in daily life, they usually do not attract clinical attention [3]. However, these anatomic variants may cause misinterpretation during the evaluation of a patient with flexor tendon injuries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 171 subjects, it was found that the FDS-V was absent in 18.6% of females and 15.3% of males and in those subjects, grip strength was significantly lower than in subject groups with independent or common (attached to FDS of fourth finger) function of FDS-V(10). Another study, in contrast, found that there was no significant difference seen in grip strength between subjects who had an FDS-V and those who did not(11). Despite the wide variability of the presence of and the conflicting information as to the functional impact of the FDS-V, current clinical examination techniques are inadequate to discriminate among the possible variations or absence of FDS(12).…”
Section: Discussionmentioning
confidence: 96%
“…10,11 Therefore the presence or absence of FDS to the little finger on the other side adds little to the assessment. Each tendon has a long vinculum proximally, where they need to accommodate more excursion, and a short vinculum more distally.…”
Section: History and Examinationmentioning
confidence: 99%